10+3x=17x+3

Simple and best practice solution for 10+3x=17x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+3x=17x+3 equation:


Simplifying
10 + 3x = 17x + 3

Reorder the terms:
10 + 3x = 3 + 17x

Solving
10 + 3x = 3 + 17x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-17x' to each side of the equation.
10 + 3x + -17x = 3 + 17x + -17x

Combine like terms: 3x + -17x = -14x
10 + -14x = 3 + 17x + -17x

Combine like terms: 17x + -17x = 0
10 + -14x = 3 + 0
10 + -14x = 3

Add '-10' to each side of the equation.
10 + -10 + -14x = 3 + -10

Combine like terms: 10 + -10 = 0
0 + -14x = 3 + -10
-14x = 3 + -10

Combine like terms: 3 + -10 = -7
-14x = -7

Divide each side by '-14'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 5x+23=82 | | 10+3x=17x+3 | | 16m^2=80 | | 5x+23=82 | | 16m^2=80 | | -1+5+x= | | 5x-15+8=14x+2 | | 2y^2-32=-32 | | 2(4x+y)= | | 4.5x-16=2.6x+3 | | 3q+9q=18 | | R^2+rst+5r+5st=0 | | -2x+7=-5x+6x+10 | | 16m^2=8m*10m | | 2(x-4)=x+4 | | 6=(-x-3) | | 2x^2-6x+32=0 | | A=a+(n-1)(d) | | -4+r= | | 14=10x+4 | | 2x-8y-6=0 | | 4d+18+9d= | | (2x-3)-(4x-5)=6y | | 7(x-4.5)=2.8 | | -4+r+20= | | t*2-1= | | n(3n+2)=1 | | x^8-15x^7-16x^6= | | 27a^3+8b^3=0 | | 17+11r+15m-2r-4m-16= | | 4x-1+x+15=180 | | 6x-7.80=97.20 |

Equations solver categories